Increasing the spatial scale of process-based agricultural systems models by representing heterogeneity: The case of urine patches in grazed pastures. (April 2017) - Snow, V.O.; Cichota, R.; McAuliffe, R.J.; Hutchings, N.J.; Vejlin, J.
Abstract: We sought to extend the spatial scale of soil-plant models by including, rather than ignoring, heterogeneity using the deposition of urine patches as an example. Our "pseudo-patches" approach preserves the most important biophysical effects but is computationally-tractable within a multi-paddock simulation. It explicitly preserves the soil carbon and nitrogen heterogeneity but does not require independent simulation of soil water and plant processes and is temporal in that the patches of heterogeneity can appear and disappear during the simulation. The approach was tested through comparison to simulations that more-closely represented field conditions and which contained independent urine patches. The testing was successful, reducing substantial error in the simulation of pasture grazed and leaching for modest increases in simulation execution time but we recommend additional testing under very low and very high stocking densities. The approach is applicable to any heterogeneity in soil nitrogen or carbon such as in spatially-managed fertiliser applications. Graphical abstract: Highlights: Most crop-soil models operate at a notional patch scale and ignore spatial heterogeneity. Inclusion of heterogeneity presents scientific, technical and practical problems. We present a method to increase the spatial scale by including some forms of heterogeneity. Urine patches drive many soil-plant processes but are usually ignored in simulation models. We apply this method to the case of urine patches in grazed pastures.